ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF THE MAGELANG CITY GOVERNMENT AREA'S FINANCIAL PERFORMANCE FOR THE 2017-2021 FISCAL YEAR - Apriliana Kurnia Ratri; Retnosari (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Regional government activities aim to accelerate the attainment of a prosperous population through improved services, empowerment, and participation of the population, followed by increasing regional competitiveness. The region always adheres to the concepts of democracy, equity, and justice, as well as the uniqueness of a region in the structure of a unitary state. In this regard, the regional government must also pay attention to the issue of the effectiveness and efficiency of regional financial management, which is an element of the principle of government activity. The aim of this research is to identify the effectiveness and efficiency of the regional financial activities of the Magelang City Government for the 2017–2021 fiscal year. This observation is made through a quantitative approach, and the data identification technique used is descriptive through the use of accumulated principles of effectiveness and efficiency analysis. The results of this observation show that regional financial activity for the level of effectiveness in the City Government of Magelang in the 2017–2021 fiscal year is classified as effective. Meanwhile, regional finance for the level of efficiency in the City Government of Magelang in 2017–2021 has three criteria, namely efficient, inefficient, and very efficient. In fact, 2020 is a year with good criteria, which is very efficient, and in 2021 it will return again with efficient criteria.